Do crop diversity and livestock production improve smallholder intra-household dietary diversity, nutrition and sustainable food production? Empirical evidence from Pakistan - Waseem, Muhammad; Li, Xiaoyun; Jamil, Ihsan; Islam, Abu Hayat Md. Saiful; Abbas, Qasir; Raza, Muhammad Haseeb; Eliw, Moataz (Frontiers in Sustainable Food Systems, 2023)
Crop diversification and livestock production is an important strategy to enhance nutrition, sustainable food production, and improve food security, especially at the smallholder household level. However, existing evidences are mixed and there are limited information about the relationship among agriculture crops, household income diversification (HID), and household dietary diversity (HDD) among smallholder farmers in developing country setting like Pakistan. Therefore, this study aims to understand the role of crop diversification (CD) on HDD, nutrition, and sustainable agriculture and food production in the context of smallholder households in Punjab, Pakistan. The study employed ordered probit regression and cross-sectional data from 450 households collected using 24-h recall method. Regression results indicate that crop diversity and intra-household dietary diversity are positively associated across adults, adolescents, and children in all the study districts. Moreover, annual income, key crops grown by the household and family education are also the significant drivers of dietary diversity. Greater travel distance between markets was the most crucial factor in all regions which significantly affect dietary diversity. The overall research findings indicated that crop diversification and livestock production in the selected areas is significantly contributing to improve nutrition and sustainable food production. Therefore this study recommends for promoting crop diversification and livestock production for sustainable agricultural development and improving nutrition in the context of developing countries like Pakistan.